Connectivity of Adaptive Leadership Behavior to Teacher Development: Perspective and Prospects for Digital Learning - Violeta Jerusalem; Emiliano T. Hudtohan (International Journal of Management and Education in Human Development, 2022)
The peculiar socio-cultural context of the pandemic situation requires schools to prepare for the new normal. This includes the challenge of technology on the delivery of online learning. The learning environment today becomes complicated when teachers virtually meet synchronously or asynchronously their students.This paper examines the virtual classrooms from a perspective of adaptive leadership, where the teacher becomes a leader, a mentor, a friend, ad a coach to the students in a learning environment. In this setting, there is a vital need for connectivity between learners and teacher to jointly explore the multiple facets of learning. The Age of Digital Technology requires a new paradigm in teacher education in online learnin; it, alters the learning patterns and behaviors of students. Hence, there is a need for teacher-learning connectivity in virtual learning. It is proposed that teacher development in embracing Adaptive Leadership to be connected with students in online classroom interaction.